Význam předoperačních konzultací - Wijeysundera, D. N (Clinical Cardiology Alert, 2010)
BACKGROUND: Preoperative consultations by internal medicine physicians facilitate documentation of comorbid disease, optimization of medical conditions, risk stratification, and initiation of interventions intended to reduce risk. Nonetheless, the impact of these consultations, which may be performed by general internists or specialists, on outcomes is unclear. METHODS: We used population-based administrative databases to conduct a cohort study of patients 40 years or older who underwent major elective noncardiac surgery in Ontario, Canada, between 1994 and 2004. Propensity scores were used to assemble a matched-pairs cohort that reduced differences between patients who did and did not undergo preoperative consultation by general internists or specialists. The association of consultation with mortality and hospital stay was determined within this matched cohort. As a sensitivity analysis, we evaluated the association of consultation with an outcome for which no difference would be expected: postoperative wound infection. RESULTS: Of 269,866 patients in the cohort, 38.8% (n=104,695) underwent consultation. Within the matched cohort (n=191,852), consultation was associated with increased 30-day mortality (relative risk [RR], 1.16; 95% confidence interval [CI], 1.07-1.25; number needed to harm, 516), 1-year mortality (1.08; 1.04-1.12; number needed to harm, 227), mean hospital stay (difference, 0.67 days; 0.59-0.76), preoperative testing, and preoperative pharmacologic interventions. Notably, consultation was not associated with any difference in postoperative wound infections (RR, 0.98; 95% CI, 0.95-1.02). These findings were stable across subgroups as well as sensitivity analyses that tested for unmeasured confounding. CONCLUSIONS: Medical consultation before major elective noncardiac surgery is associated with increased mortality and hospital stay, as well as increases in preoperative pharmacologic interventions and testing. These findings highlight the need to better understand mechanisms by which consultation influences outcomes and to identify efficacious interventions to decrease perioperative risk.
Keywords: Length of Stay; Confounding Factors, Epidemiologic; hodnocení rizik; faktory vyvracející (epidemiologie); chirurgie operační; Comorbidity; Male; retrospektivní studie; Risk Assessment; odds ratio; Surgical Procedures, Operative; chronická nemoc; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; Chronic Disease; délka pobytu; komorbidita; výsledky a postupy - zhodnocení (zdravotní péče); předoperační péče; konziliární vyšetření a konzultace; lidé; ženské pohlaví; studie případů a kontrol; Humans; Sensitivity and Specificity; senzitivita a specificita; vnitřní lékařství; Confidence Intervals; Outcome and Process Assessment, Health Care; Financing, Organized; Odds Ratio; Internal Medicine; Retrospective Studies; Ontario; Female; Preoperative Care; financování organizované; lidé středního věku; Referral and Consultation; interval spolehlivosti; Middle Aged